Analisis Peluang Siaran Jambi TV di Era Industri 5.0 - Setiawan, Ahmadi; Maulana, Arif; Fabri, Erlinda Aidil; Yunita, Nurma; Khoiri, Umul (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
Jambi TV is a television station that plays a crucial role in broadcasting media in the Jambi Province, Indonesia. The general aspects of Jambi TV include various elements that influence its operations and its contribution in providing information, entertainment, and services to the people of Jambi. This writing will discuss several key aspects related to Jambi TV, including the station's profile, flagship programs, contribution to broadcasting news and information, as well as its social impact on the local community. This report will also address the trends and challenges faced by Jambi TV in the current era of Industry 5.0, as well as its strategic role in meeting the needs of the audience in the Jambi region. Through a deeper understanding of the general aspects of Jambi TV, we can appreciate its important role in regional broadcasting and its impact on the local community.